ANALYSIS OF BREAK-EVEN POINT IN CV.BATA CIKARANG INDONESIA - Jamaludin, Agus (International Journal of Research -GRANTHAALAYAH, 2020)
This study was obtained from the balance sheet and income statement of CV Bata Cikarang Indonesia in 2018, then the title is: Break Event Point Analysis on CV Bata Cikarang Indonesia. The goal is to find out the performance of CV Bata Cikarang seen from the company’s Break Event Point. The research method is Field Research by visiting research objects and conducting interviews, and Library Research by exposing existing data in the form of Balance Sheet and Profit and Loss reports, and sales of data in the form of quantitative data and in the form of descriptive. Break Event Point analysis is performed to determine the company’s financial performance, can also be used as a reference in making decisions that affect the company’s future. As for the results in 2017 the BEP unit is 1,055,194 and the rupiah BEP is IDR 422,077,922 and 2018 the BEP unit = 1,027,397.26 and the IDR BEP is IDR 462,392,108.